Perlindungan Hukum bagi Konsumen Marketplace terhadap Tidak Tercantumnya Berat Bersih dalam Produk Makanan Kemasan Menurut Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Eugenia Giovani Anggasta Putri Banggung; Siti Ramlah Usman; Helsina Fransiska Pello (Lembaga Pengembangan Kinerja Dosen, 2024)
Along with technological developments, buying and selling transactions are also influenced by technological developments. In the past, buying and selling transactions were carried out in markets, shops, stalls, but nowadays sellers and buyers carry out buying and selling transactions online (e-commerce), one of which is the marketplace. The increasingly consumerist life of society in the era of globalization has resulted in reduced public awareness of the packaged food products they consume. There are problems that often arise regarding the inclusion of net weight. For example, business actors do not include net weight information on packaged food products. This problem is certainly detrimental to the public because they do not know the actual net weight of the food product. The main problems in this research are (1) What is the legal protection for marketplace consumers against packaged food products that do not include net weight? (2) What factors cause packaged food product businesses in the marketplace to not include net weight? This research is empirical juridical research, meaning that analyzing problems is carried out by combining legal materials which are secondary data with primary data obtained in the field. The legal sources and materials used are primary and secondary legal materials. The results of this research indicate that legal protection for marketplace consumers for packaged food products that do not include net weight according to Law Number 8 of 1999 has not been implemented which has different (varied) answers from consumers because some consumers say that there are still business actors who have not know about the rules for including net weight and from the Kupang City Industry and Trade Service itself which has never handled cases regarding business actors selling packaged food products that do not include net weight, in other words there have been no complaints.